Kreativitas Guru Dalam Membentuk Karakter Rasa Ingin Tahu Melalui Metode Gamifikasi - Yuna Yulianti; Sulistia Wati; Dina Rahmawati; Sari, Nur Indah; Sri Ulandari (PT. Intelek Cendikiawan Nusantara, 2024)
The role of a teacher in the world of education is not only teaching subjects, but also shaping children’s character. One of the most important character traits to be develoved is curiosity. This study conducted literature research by looking for previous references to theories related to the theme of the discussion. The literature review outlines the findings of previous research and is adapted to future research. Gamification is an innovative educational approach than can make learning more fun and motivate children. Teachers who are can design educational games that are engaging, interactive, and support active learning. Through gamification, teachers can create learning environment that stimulates children’s interest and desire to explore deeper knowledge. This approach is expected to develop children’s curiosity, critical thinking, and creativity in problem solving. Further research is needed to assess the effectiveness of the gamification method in shaping children’s curiosity and its impact on learning outcomes.